Antioxidants in Health and Disease Volume 2 - Maurizio Battino (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Several epidemiological studies have demonstrated that oxidative stress is associated with a number of health disorders, including cardiovascular malfunction, certain types of cancer, diabetes mellitus, many other auto-immune diseases, and even ageing. The body possesses multiple mechanisms to counteract oxidative stress, which employ antioxidant compounds that are either naturally generated in situ (endogenous antioxidants) or externally supplied through food (exogenous antioxidants). These antioxidants are able to counteract oxidative stress, thanks to their ability to neutralize excess free radicals and protect the cellular lipids, proteins, and DNA from molecular damage. Exogenous antioxidants from the diet are of increasing interest because of their beneficial role in maintaining good health and in preventing chronic diseases. Indeed, a diet rich in dietary antioxidants, especially from fruits and vegetables, has been correlated with a successful prevention and lower incidence of several degenerative pathologies, including obesity, diabetes, cardiovascular diseases, and cancer. This Special Issue of Nutrients welcomes the submission of manuscripts, either describing original research or reviewing scientific literature, examining the role of diets rich in antioxidant compounds in the prevention of chronic diseases and the characteristics of the antioxidants included in such diets.